Urban regeneration (Thomas Telford, 1988)
Chapters cover topics such as causes and characteristics of urban decay, land assembly issues, organizations for regeneration and incentives, amongst others.
Keywords: Urban renewal -- Great Britain.; elektronické knihy; electronic books